2020
DOI: 10.3354/aei00347
|View full text |Cite
|
Sign up to set email alerts
|

Biological controls to manage Acropora-eating flatworms in coral aquaculture

Abstract: Coral aquaculture is expanding to supply the marine ornamental trade and active coral reef restoration. A common pest of Acropora corals is the Acropora-eating flatworm Prosthiostomum acroporae, which can cause colonial mortality at high infestation densities on Acropora spp. We investigated the potential of 2 biological control organisms in marine aquaria for the control of P. acroporae infestations. A. millepora fragments infested with adult polyclad flatworms (5 flatworms fragment-1) or single egg clusters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For example, in Australia, dwarf gourami ( Trichipodus lalius ) can transmit infectious kidney and spleen necrosis virus (genus Megalocytivirus, Iridoviridae ) to domestic fishes, often with detrimental impacts including disease outbreaks in iconic species such as Murray cod ( Maccullochella peelii ) [23, 24]. Moreover, tropical wrasses (Labridae) have been considered effective biological control agents in aquaculture for their natural ability to consume pests [25]. However, temperate cleaner wrasses have been reported to be important drivers of outbreaks of viral haemorrhagic septicaemia virus ( Rhabdoviridae ) in farmed salmonids [26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Australia, dwarf gourami ( Trichipodus lalius ) can transmit infectious kidney and spleen necrosis virus (genus Megalocytivirus, Iridoviridae ) to domestic fishes, often with detrimental impacts including disease outbreaks in iconic species such as Murray cod ( Maccullochella peelii ) [23, 24]. Moreover, tropical wrasses (Labridae) have been considered effective biological control agents in aquaculture for their natural ability to consume pests [25]. However, temperate cleaner wrasses have been reported to be important drivers of outbreaks of viral haemorrhagic septicaemia virus ( Rhabdoviridae ) in farmed salmonids [26].…”
Section: Introductionmentioning
confidence: 99%
“…The most studied cases of predation by polyclads are in relation to the damage they cause to the commercial shellfish industry, and to a lesser extent the coral aquaculture industry [42][43][44][45][46][47]. Globally, shellfish stocks such as oysters (pearl and food), mussels and clams suffer predation by flatworms, with members of the family Stylochoidea typically responsible for the majority of damage [48,49].…”
Section: Commercial Pestsmentioning
confidence: 99%
“…The peppermint shrimp Lysmata vittata (Stimpson, 1860) and sixline wrasse Pseudocheilinus hexataenia (Bleeker, 1862) were suggested by Barton et al . (2020) as suitable biological control candidates in captive systems. The authors found L. vittata removed 82.0 ± 26.76% (mean ± SD) of egg capsules laid on Acropora skeleton and 63.67 ± 43.48% of flatworm individuals from Acropora millepora fragments.…”
Section: Acoelamentioning
confidence: 99%